2020
DOI: 10.1038/s41598-020-60260-7
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned place preference reveals ongoing pain in calves 3 weeks after disbudding

Abstract: Hot-iron disbudding, a routine procedure that prevents horn bud growth through cauterization, is painful for calves. The resulting burns remain sensitive to touch for weeks, but it is unknown whether calves experience ongoing, non-evoked pain. We evaluated conditioned place preference for analgesia in 44 calves disbudded or sham-disbudded 6 hours (Day 0) or 20 days (Day 20) before testing (n = 11/ treatment). Calves were conditioned to associate the effects of a lidocaine cornual nerve block with the location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 39 publications
(55 reference statements)
3
29
0
Order By: Relevance
“…Most studies using wound-directed behaviors and cortisol plasma levels did not explore evidence of pain beyond 24 h [14,42]. Some calves experienced reduced consumption of the sweet solution for as long as 5 days, a result consistent with other recent reports showing longlasting pain after hot-iron disbudding [43][44][45]. These results, along with the negative judgment bias observed after disbudding in previous studies [16,46], suggest that the procedure may induce persistent pain potentially leading to depressive-like mood in dairy calves.…”
Section: Plos Onesupporting
confidence: 70%
“…Most studies using wound-directed behaviors and cortisol plasma levels did not explore evidence of pain beyond 24 h [14,42]. Some calves experienced reduced consumption of the sweet solution for as long as 5 days, a result consistent with other recent reports showing longlasting pain after hot-iron disbudding [43][44][45]. These results, along with the negative judgment bias observed after disbudding in previous studies [16,46], suggest that the procedure may induce persistent pain potentially leading to depressive-like mood in dairy calves.…”
Section: Plos Onesupporting
confidence: 70%
“…Heifers received 1 mg/kg oral meloxicam immediately after disbudding. There is good evidence that pain persists in the weeks after disbudding [28][29][30], long after the drugs' analgesic effects have dissipated.…”
Section: Plos Onementioning
confidence: 99%
“…A recent study showed that providing an NSAID renders the procedure less aversive [ 37 ], suggesting that a multi-modal pain mitigation strategy may dampen the negative affective experience associated with the procedure, at least for the first day after the procedure. However, these drugs only mitigate the pain for hours to days (depending on the NSAID); whereas, the pain associated with disbudding has been reported to last for weeks [ 38 , 39 ]. These lines of evidence show that pain mitigation helps but does not completely suppress the pain associated with these procedures.…”
Section: Physical Mutilationsmentioning
confidence: 99%